Influence of moisture content on the mechanical properties of Guadua Culms - Martha Lissette Sánchez Cruz; Luz Yolanda Morales (Inge-Cuc, 2019)
Introduction−Due to its earthquake behavior, the use of bamboo for structural purposes has increased in the latest decades, mainly in South American countries, in which, their employment, has been standardized in the design bases. However, for the efficient use of bamboo as a construction material, it is necessary to consider that being a natural material, volumetric variations can occur, especially when the material is subjected to changes in moisture between the saturation point of the fibers and the equilibrium moisture.Objectives−The objective of this paper is to evaluate the influence of the moisture content on the mechani-cal properties of elements extracted from the bottom, middle, and top of bamboo culms.Methodology−For the study, research is carried out with a quantitative approach. The experimental charac-terization was focused on the determination of compres-sion, bending, and shear strength, according to the rec-ommendations of the Colombian Technical Standards.Results−Results allow verifying that bamboo elements are susceptible to vary their strength and stiffness de-pending on the equilibrium moisture of the region to be considered in the structural design. Conclusions−Theinfluence of the moisture content on the mechanical properties of elements extracted from the bottom, middle, and top of bamboo culms was evalu-ated. The experimental characterization was focused on the determination of compression, bending, and shear strength. From the results, it is possible to verify that an increase in the moisture content reduces the mechanical strength of the material. The decrease in the values of maximum stress is more significant for moisture values between 12 % and the saturation point of the fibers and is accompanied by important dimensional changes that impair the mechanical performance of the material. The results show that above the point of saturation of the fibers the mechanical behavior of the culms is not modified